Covid-19 Impact on Divorce Case Using Sentiment Analysis - Agung Handayanto; Padmi Dhyah Yulianti; Khoiriya Latifah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2021)
Covid-19 is a human tragedy. Covid 19 made the world experiences stress. The presence of covid 19 has made individuals and families face various threats such as physical, psychlogical, economic and educational. The study noted an increase in the divorce rate during the pandemic. Divorce will have a significant impact on both spouses and children. Therefore it is necessary to design a system to predict the divorce rate in the new normal, by determining the precision of the impcat of divorce in the post covid periode using polarity sentiment analysis methods as an effort to prevent divorce. The primary data collection methods is taken from the data of the applicat filling a lawsuite at the Semarang City Religious Court Office and using external data from social media (twitter API). Based on the results of research, the covid-19 pandemic has a negative impact on society of 0,8.